An illustrated cultural history of England - Halliday, Frank Ernest, 1903-1982 (London : Thames and Hudson, 1981)
Preface - Prehistoric beginnings - Roman Britain 50-450 -The Anglo-Saxons 450-1066 - The Anglo-Normans 1066-1200 - The early Middle Ages 1200-1350 - The later Middle Ages 1350-1500 - The early Tudors 1485-1558 - The Elizabethans 1558-1603 - The early seventeenth century 1603-1660 - The later seventeenth century 1660-1714 - The eighteenth century 1714-1789 - The Romantics 1789-1837 - The Victorians 1837-1901 - The twentieth century
Bibliography: p. [6]
Keywords: Art, English; England -- Intellectual life